Metabolism of azo dyes by Lactobacillus casei TISTR 1500 and effects of various factors on decolorization - Phisit Seesuriyachan (2018)
Lactobacillus casei TISTR 1500 was isolated from soil of a dairy wastewater treatment plant and selected as the most active azo dye degrader of 19 isolates. Growing cells and freely suspended cells of this strain completely degraded methyl orange, thereby decolorizing the medium. The strain stoichiometrically converted methyl orange to N,N-dimethyl-p-phenylenediamine and 4-aminobenzenesulfonic acid, which were identified by HPLC, GC, and GC-MS analyses. The enzyme activity responsible for the cleavage of the azo bond of methyl orange was localized to the cytoplasm of cells grown on modified MRS medium containing methyl orange. The effect of sugars, oligosaccharides, organic acids, metal ions, pHs, oxygen and temperatures on methyl orange decolorization by freely suspended cells was investigated. The optimal conditions for the decolorization of methyl orange by the Lactobacillus casei TISTR 1500 are incubation at 35 °C and pH 6 with sucrose provided as the energy source. © 2006 Elsevier Ltd. All rights reserved.